2014
DOI: 10.1109/tsm.2014.2335156
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pad Topography in Chemical-Mechanical Polishing

Abstract: In this paper, the role of pad topography on material removal rate (MRR) in chemical-mechanical polishing (CMP) is investigated. First, based on the mechanics of pad/particle and particle/wafer sliding contacts at an asperity of the polishing pad a new MRR model is developed. The model is then extended to multi-asperity contacts, taking into account the statistics of the asperity heights. The single-asperity model reveals that the removal rate at relatively low pressure strongly depends on the pressure and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 46 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…The developed lab-scale technique proposed in this study consisted of equipment that was deliberately grouped to meet the purpose for which it was combined. The most important component in CMP is the polishing pad, and its characteristics must be provided in detail in terms of the structure and materials [21]. The design of the polishing pad utilized in this work consisted of a surface layer of flexible brush-like microfibers with the ability to efficiently carry the nanoscale abrasives in the slurry independent of the sample down pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The developed lab-scale technique proposed in this study consisted of equipment that was deliberately grouped to meet the purpose for which it was combined. The most important component in CMP is the polishing pad, and its characteristics must be provided in detail in terms of the structure and materials [21]. The design of the polishing pad utilized in this work consisted of a surface layer of flexible brush-like microfibers with the ability to efficiently carry the nanoscale abrasives in the slurry independent of the sample down pressure.…”
Section: Methodsmentioning
confidence: 99%
“…At 80 degrees, it was found that the surface became blunt due to the excessive elevation and the formation of large asperities via the fusion of multiple asperities, as described above. Generally, the contact state of the asperities is closely related to the removal rate in the CMP process [20,21]. is believed to be affected by changes in the asperities' contact states due to the asperity angles, as described in this section, and the experiment was performed to examine this effect.…”
Section: Scanning Electron Microscope (Sem) and Micro-ctmentioning
confidence: 99%
“…In the CMP process, the contact among pad asperities, glass substrates, and abrasive particles is rather complicated. Numerous abrasive particles are captured by the micro contact spots that formed between polishing pad asperities and glass substrate 12 . These trapped abrasive particles can be considered as part of the pad asperity itself and provide the “chemical tooth” that bonds with glass surface 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous abrasive particles are captured by the micro contact spots that formed between polishing pad asperities and glass substrate. 12 These trapped abrasive particles can be considered as part of the pad asperity itself and provide the "chemical tooth" that bonds with glass surface. 13,14 Therefore, the material removal for a given site on the glass surface is a superposed renewal process, which combines the successive scraping action of entrapped abrasive particles and the transient chemical activation of surface atoms by the polishing slurry.…”
mentioning
confidence: 99%